(untitled) (KYAMC Journal, 2025)
Background: Acute lymphoblastic leukemia (ALL) is among the most common and curable cancers in pediatric populations. A notable complication that can occur during its treatment is coagulopathy, often resulting from the use of chemotherapeutic drugs, especially L-asparaginase (L-aspa). This condition has the potential to negatively influence the overall prognosis of the illness. Objective: To assess the frequency, clinical presentations and risk factors associated with coagulopathy in pediatric patients diagnosed with acute lymphoblastic leukemia during induction phase of chemotherapy with L-Asparaginase. Materials and Methods: This observational study was carried out from October 2017 to November 2018 within the Department of Paediatric Haematology and Oncology at BSMMU. The study included children under 18 years of age who were newly diagnosed with acute lymphoblastic leukemia and had received induction chemotherapy that included L-Asparaginase (L-aspa). These patients were then monitored and assessed for coagulopathy. Results: Among the 80 patients studied, coagulopathy was observed in 38 individuals (47.5%). The analysis did not identify age, sex, initial white blood cell count, platelet count, lineage of acute lymphoblastic leukemia (ALL), treatment regimen or neither central nervous system status as risk factors. Notably, patients with T cell lineage ALL exhibited a higher percentage of coagulopathy (69.2%). Dry bleeding i.e. Petechiae, Purpura, Echymosis were the most common bleeding type. Platelet count was found significantly low with bleeding at diagnosis but initial INR, APTT had no significant relation with bleeding. After 2nd, 4th and 6th L-aspa INR and APTT were to be found significantly high in bleeding but they were not found significant in other stages. Conclusion: In this study coagulopathy was found in significant number of cases. Rate of coagulopathy was higher at diagnosis and remains high up to 6th dose of L-aspa. No risk factor for coagulopathy had been identified as significant. Dry bleeding was more common than life threatening wet bleeding. PT and APTT were to be found as significant predictors for bleeding after 2nd, 4th and 6th dose of L-aspa. KYAMC Journal Vol. 16, No. 01, April 2025: 14-19